ANALISIS STRUKTURAL C.LEVI STRAUSS PADA CERITA SASTRA LISAN JAWA TIMUR “BABAT ALAS GAYAM” - Umi Rosidah (Indonesian language and literature education program Majapahit Islamic University, 2023)
Oral literature is part of the ancestral heritage that has been passed down from generation to generation. Every region of Indonesia has oral literature with its own uniqueness which cannot be separated from the levels within it. This research reveals the structural level of East Javanese oral literature entitled Babat Alas Gayam using the theory of C. Levi Strauss. Data was obtained through interviews with sources. The data source in this study is the oral literary story Babat Alas Gayam. This study also uses listening and note-taking techniques. The data collection steps carried out by researchers are as follows. First, conduct interviews with sources. Second, transcribe the data. Third, find data. Fourth, summarize the data. Next, the following is the data analysis procedure carried out by the researcher. First, identify the data. Second, classify the data. Third, describe the data. Lastly, make a conclusion. This study produces information regarding the geographical, techno-economic, cosmological and sociological levels contained in the oral literature of Babat Alas Gayam.